Diagnostic yield of the Kveim test in sarcoidosis patients: Kveim test - Tetikkurt, Cuneyt; Yanardag, Emre; Bilir, Muammer; Yanardag, Halil; Kimyon, Ugur (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: Sarcoidosis is a granulomatous disorder of unknown etiology characterized by the existence of non-caseating granulomatous inflammation. Diagnosis can be challenging due to the presence of comprehensive clinical, laboratory, and radiologic manifestations. We have evaluated the diagnostic yield of the Kveim test and compared this test with the other conventional laboratory modalities. Our aim was to reach the highest level of diagnostic confidence acknowledging the absolute uncertainty in diagnosis with the current diagnostic enterprises. Methods: Medical records of 300 sarcoidosis patients were reviewed. Patients were classified into two categories as the conventional laboratory and the Kveim test group to compare the diagnostic yield. Results: Sensitivity of the Kveim test was 76.4% while the conventional laboratory tests provided a 64% diagnostic yield. The conventional tests had a low diagnostic rate in the early disease stages. Kveim test revealed a high yield diagnosis for all stages of sarcoidosis. Integrated assessment of the two modalities reached a 96.8% sensitivity and a 94,6% specificity. Conclusions: Conventional laboratory modalities were useful for the assessment of disease activity and identification of organ involvement. Kveim test revealed a significant diagnostic yield for all stages of sarcoidosis. The lowest output was achieved in stage IV patients due to the waning of active granulomatous inflammation. The highest diagnostic sensitivity was obtained by an integrated analysis of the conventional laboratory and the Kveim test results for all aspects of sarcoidosis.